1996
DOI: 10.1111/j.1600-079x.1996.tb00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin implants on winter fur growth and testicular recrudescence in adult male raccoon dogs (Nyctereutes procyonoides)

Abstract: The effects of melatonin implants were investigated on winter fur growth, monitored by counting growing and mature hairs per bundle and testicular recrudescence, judged by testis width, score count of spermatogenesis, and serum testosterone in the adult male raccoon dogs. Melatonin administration in July highly elevated melatonin concentrations in serum and urine and induced an earlier decrease in prolactin secretion (August in the treated group vs September in the control group), winter fur growth (July-begin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…The cyclical alternation in the growth and involution of testes is a well-known phenomenon [5], and the seasonality of testicular mass and spermatogenesis shown in this study is in general agreement with some reports on this species [36][37][38]. We observed testicular recrudescence and regression in the adult male raccoon dog as judged by testis weight, size and score count of spermatogenesis with highest values of weight and size in the mating season.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The cyclical alternation in the growth and involution of testes is a well-known phenomenon [5], and the seasonality of testicular mass and spermatogenesis shown in this study is in general agreement with some reports on this species [36][37][38]. We observed testicular recrudescence and regression in the adult male raccoon dog as judged by testis weight, size and score count of spermatogenesis with highest values of weight and size in the mating season.…”
Section: Discussionsupporting
confidence: 92%
“…The raccoon dog (Nyctereutes procyonoides) is a typical seasonal breeder with a short sexually active period lasting about 6 weeks in February and March, followed by a long period of sexual dormancy from April to January [38]. During the mating period, male raccoon dogs are willing to mate and produce mature spermatozoa.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…C y c l i c a l t e r n a t i o n b e t w e e n g r o w t h a n d i n v o l u t i o n o f t h e t e s t e s i s a w e l l -k n o w n phenomenon [29]. The seasonality of testes mass shown in the present study is in agreement with extensive reports on this species [15][16][17][18][19] [16]. In the present study, we observed testicular recrudescence and regression in the male raccoon dog as judged by testis weight and size and seminiferous tubule diameter, with the highest values seen during the breeding season.…”
Section: Discussionsupporting
confidence: 82%
“…In China, there are marked seasonal changes in the serum testosterone concentrations of farmed raccoon dogs, with a significant rise in October, a peak in the early breeding season, and a rapid drop at the end of the breeding season [17]. Although several observations about reproduction in the raccoon dog have been reported recently [18][19][20][21][22][23], there are still many gaps in the understanding of the mechanisms of reproduction, especially concerning secretion of inhibin in the development process of the testes. The aim of the present study was to investigate the localization of inhibin subunits in the testes during the non-breeding and breeding seasons and to elucidate the relationship between inhibin and reproductive function in wild male raccoon dogs.…”
mentioning
confidence: 99%